Development of Website-Based Learning Media for Graphic Design and Multimedia Courses in the Digital Business Study Program - I Putu Okta Priyana; Made Ayu Jayanti Prita Utami; Upayana Wiguna Eka Saputra; Ni Putu Maha Lina; Gede Sedana Wibawa Yasa (Universitas Pendidikan Ganesha, 2025)
Limitations of conventional learning media in Graphic Design and Multimedia courses result in limited access flexibility, low interactivity, and suboptimal development of students’ problem-solving skills. Therefore, adaptive, interactive, and curriculum-aligned learning media are needed in vocational education. This study aims to develop and evaluate interactive, engaging, and appropriate web-based learning media that meet student needs and curriculum requirements, while also testing the effectiveness and user satisfaction level in supporting problem-solving-based learning. This is a research and development study using the ADDIE model, which includes the stages of needs analysis, interface and content design, prototype development, implementation, and evaluation. The research subjects involved 62 second-semester students who took the Graphic Design and Multimedia course. Data were collected through a needs analysis questionnaire, media assessment questionnaire, and learning outcome tests in the form of pre-tests and post-tests. Data analysis was performed using quantitative descriptive analysis based on percentages and learning outcome comparisons. The results of the study indicate that the web-based learning media developed can improve student understanding, elicit positive responses to aspects of interactivity, clarity of material, and ease of access, and support more independent and contextual learning. The conclusion of this study confirms that web-based learning media are effective in improving the quality of vocational learning that is adaptive to technological developments and industry needs.